Analisis Kurikulum “Merdeka Belajar” di SMPN 3 Plered pada Era Society 5.0 - Ngaripin (Sekolah Tinggi Ilmu Tarbiyah Tihamah, 2023)
“Merdeka Belajar” curriculum is also expected to be able to produce output from high moral education. “merdeka belajar”curriculum strives for the role of technology, which is a human need today to be integrated in the era of society 5.0. The research method used in this research is descriptive qualitative research. The results of the research show that at the planning stage all school stakeholders were initiated by the Deputy Head of Curriculum to compile the things needed in learning. Starting from learning tools, media and teacher readiness in carrying out learning for one academic year which will take place with the concept of “merdeka belajar” Curriculum. At the implementation stage, the implementation of this independent curriculum also had an impact felt by students, educators, and other educational staff. The perceived impact is also divided into two, the positive impact and the negative impact. Factors that become obstacles in the application of independent learning is the lack of understanding that educators, students, even parents have, which hinders the purpose of the process of implementing independent learning. As well as the lack of infrastructure available in the implementation of “merdeka belajar” curriculum. The conclusion of this research is that “merdeka belajar” curriculum implemented at SMPN 3 PLERED is running as it should, it only needs improvement in terms of understanding and teaching materials to support the implementation of the proper independent curriculum.